Analisa SWOT dalam Perencanaan Strategi Pengembangan Ruang Publik Terpadu Ramah Anak (RPTRA) di Kelurahan Cempaka Putih Timur (International Forum of Researchers and Lecturers, 2025)
This study aims to conduct a SWOT analysis in planning the development strategy of Child-Friendly Integrated Public Space (RPTRA) in East Cempaka Putih Village. RPTRA is a public facility designed to support children's growth and development, improve the quality of the social environment, and strengthen relationships between residents in urban areas. Despite having great potential in encouraging social development, the existence of RPTRA still faces various challenges in its implementation, such as limited facilities, lack of community participation, and weak management systems. This study uses SWOT analysis methods to identify the strengths, weaknesses, opportunities, and threats faced by RPTRAs in the region. The data collection technique was carried out through direct observation at the location, documentation, and interviews with various stakeholders, including the village government, RPTRA managers, and the community using the facility. The results of the analysis show that the main strength of RPTRA lies in the existence of basic infrastructure, strategic location, and policy support from local governments. Weaknesses include lack of operational funds, limited educational facilities, and lack of training for managers. Opportunities can be seen from increasing public awareness of the importance of child-friendly public spaces and the opening of potential partnerships with the private sector. The threat comes from the potential for vandalism, lack of social control, and the risk of non-functional use of space. This research provides a number of strategic recommendations that include multi-stakeholder collaboration, active community involvement, and capacity building of human resources in the management of RPTRA. In addition, the proposed long-term strategies include the integration of family empowerment programs, the improvement of educational technology-based facilities, and the strengthening of regulations that support the sustainability of the RPTRA program. The implications of this study are expected not only to have an impact on optimizing the function of RPTRA locally, but also to become a model for the development of child-friendly public spaces in other urban areas. This research contributes to the literature on inclusive urban development oriented towards child welfare and strengthening community social cohesion.